Pengaruh Fraud Hexagon dan Board Gender Diversity Terhadap Fraudulent Financial Statement pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Florensia, Kimberly; Nizarudin, Abu; Karmawan, Karmawan (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Fraud is divided into 3 categories namely asset misappropriation, corruption, and fraudulent financial statements, but there is a category that has the lowest percentage of cases with the largest loss impact, namely fraudulent financial statements. This study aims to determine and analyze the effect of financial target, external pressure, ineffective monitoring, change in auditor, change in director, frequent number of CEO’s picture, cooperation with government project and board gender diversity on fraudulent financial statement. This study uses a quantitative approach using secondary data. The population in this study were 47 mining companies listed on the Indonesia Stock Exchange in 2019-2023, then samples were taken using purposive sampling or judgmental sampling techniques as many as 29 mining companies during the 2019-2023 period so that the number was 145 samples. The data analysis technique used is logistic regression analysis. Based on the results of the study, it shows that the variables of financial targets and external pressure have a positive effect and significant on fraudulent financial statements, while the variables of variabel ineffective monitoring, change in auditor, change in director, frequent number of CEO’s picture, cooperation with government project and board gender diversity have no effect on fraudulent financial statements.